Analiza dvoslojnih prostorskih nosilcev s podajnim stikom - Udovč, Gregor (Gradbeni vestnik, 2022)
The article presents a new mathematical and numerical model for the analysis of two-layer spatial beams with inter-layer slip. There are several novelties in the presented mathematical and numerical model. The first novelty is that the model allows the analysis of the influence of shear deformations on the stiffness of two-layer spatial beams. The second novelty of the model is that the inter-layer slip can take place in both longitudinal and transverse directions, while inter-layer slip in perpendicular direction is not possible. Yet another important novelty of the model is a consistent separation of the basic equations of the model into two unrelated groups. The negative effect of singularities due to the constraint equations, which would otherwise occur when solving the model equations, is thus avoided. The equations of the presented numerical model are solved by applying the finite element method. Thus, a new family of deformation based finite elements has been developed, in which all the deformation quantities of the beam model are interpolated with Lagrange polynomials of arbitrary degree. By introducing a new deformation based finite element we are able to avoid all types of blocking typical for displacement-based finite elements. The convergence and parametric studies, presented in this article, show: (i) that the deformation based finite elements are very accurate and therefore suitable for the analysis of two-layer spatial beams, (ii) that the inter-layer slip significantly affects the values of physical quantities and therefore has to be considered in the analysis, and (iii) that shear deformations have smaller effect on the stiffness of the two-layer spatial beams than on the stiffness of homogeneous spatial beams.
Keywords: deformacijski končni element; kompozitni nosilci; podajen stik; prostorska analiza; strižne deformacije